Faktor-Faktor Yang Mempengaruhi Pendapatan Asli Daerah Provinsi Jawa Barat Menggunakan Least Absolute Shrinkage And Selection Operator - Tripena, Agustini; Alifah, Alifah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
ROI is one of the milestones of a region's independence. Regional Original Income (ROI) is a source of regional income originating from the regional economic activities themselves. ROI sources consist of regional taxes, regional levies, regional wealth management results, and other legitimate regional income. This research aims to analyze the influence of the number of work force, population, number of star hotels, number of non-star hotels and number of industries on ROI in West Java Province in 2018. The analysis was carried out using the LASSO regression method with the LAR algorithm to handle cases of multicollinearity found in the independent variables number of workforce and population. The research results show that the variables of population and number of star hotels have a significant effect on ROI.